Studi Persamaan Empiris Percepatan Tanah Berbasis Data Gempa Bumi Di Wilayah Bali Periode 2008-2016 - I Putu Arix Putra Wiguna; I Made Yuliara (Universitas Hamzanwadi, 2019)
The earthquake was the most common natural disaster in Indonesia, one ofwhich was the Province of Bali. The southern part of Bali is a meeting area of two earth plates (subduction zones) between the Eurasian and Indo-Australian plates and in the northern region there is a back arc thrust fracture which results in earthquake frequencies in the Bali area. One of the parameters that is very instrumental in determining the level of damage to land and buildings that occur on the surface of the earth due to earthquake shocks is the acceleration of the soil. A research has been conducted which aims to find out the empirical equation of land acceleration for Bali in the 2008-2016 period, namely by determining the empirical equation of land acceleration (PGA) conducted using magnitude parameters, hypocenter distance and PGA (observation) values in 2008-2016 with coordinates 70-120 LS and 1130-1180 BT. Through the regression analysis approach, to obtain the empirical equation of land acceleration in the Bali region is ð‘™ð‘œð‘”10(ð‘ƒðºð´) = (âˆ’1,89) ð‘™ð‘œð‘”10(ð‘…) + (0,71) ð‘šð‘ + 1,18. Then several approaches and correlation analysis are performed to see the compatibility of the new empirical equation with the existing one.